Laporan Penyuluhan Perilaku Hidup Bersih dan Sehat Bagi Masyarakat Dikanagarian Ampiang Parak Kecamatan Kesugihan Kab. Cilacap Tahun 2022 - Ruman; Dwi Septian (Pusat Riset dan Inovasi Nasional, 2022)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health for everyone. Healthy conditions do not happen immediately, but efforts must always be made to move from being unhealthy to living a healthy life and creating a healthy environment. This effort must start from instilling a healthy mindset in society which must be started and worked on by oneself. This effort is to realize the highest level of public health as an investment for the development of productive human resources. Meanwhile, public awareness of health and a clean and healthy lifestyle, especially in rural communities, is still very low. For this reason, providing education regarding clean and healthy living behavior is expected to be an effort to make the public aware of the importance of implementing clean and healthy living behavior in everyday life as well as providing knowledge on how to make it happen so that a society that cares about health can be created.